Comparative Study of Self-esteem, Happiness, Psychological well-being and Satisfaction with life in Working and Non -Working Women - Kaur, Harneet (My University, 2021)
The aim of the present study is to investigate the difference between working and non-working women of three age groups with respect to self -esteem, happiness, psychological wellbeing, satisfaction with life. The sample consists of 369 women out of which ,181 were workingwomen and 188 were non- working women. 137 women were of age range of 22 to 34 years ,103 women were of age range of 35 years to 44years and 129 women were of age range of 45 years to 60 years and the data was collected online via Google forms. The data was collected using the Rosenberg self- esteem scale, Oxford happiness scale, Ryff’s psychological well being scale, Satisfaction with life scale. The data was analyzed using descriptive statistics and analysis of variance. The findings suggest that middle age working women have high level of self -esteem, happiness, psychological well -being and satisfaction with life than young and late middle age working women. It is also revealed that working women have higher self esteem, happiness, psychological well -being and satisfaction with life than non-working women.
Keywords: Self - esteem; Happiness; Psychological wellbeing; Satisfaction with life; Working women; Non- working women